A Requirement for Global Transcription Factor Lrp in Licensing Replication of Vibrio cholerae Chromosome 2 - Ciaccia, Peter N.; Ramachandran, Revathy; Chattoraj, Dhruba K. (Frontiers in Microbiology, 2018)
The human pathogen, Vibrio cholerae, belongs to the 10% of bacteria in which the genome is divided. Each of its two chromosomes, like bacterial chromosomes in general, replicates from a unique origin at fixed times in the cell cycle. Chr1 initiates first, and upon duplication of a site in Chr1, crtS, Chr2 replication initiates. Recent in vivo experiments demonstrate that crtS binds the Chr2-specific initiator RctB and promotes its initiator activity by remodeling it. Compared to the well-defined RctB binding sites in the Chr2 origin, crtS is an order of magnitude longer, suggesting that other factors can bind to it. We developed an in vivo screen to identify additional crtS-binding proteins and identified the global transcription factor, Lrp, as one such protein. Studies in vivo and in vitro indicate that Lrp binds to crtS and facilitates RctB binding to crtS. Chr2 replication is severely defective in the absence of Lrp, indicative of a critical role of the transcription factor in licensing Chr2 replication. Since Lrp responds to stresses such as nutrient limitation, its interaction with RctB presumably sensitizes Chr2 replication to the physiological state of the cell.